Inkjet Printing of Quasi‐2D Perovskite Layers with Optimized Drying Protocol for Efficient Solar Cells. Issue 12 (6th July 2022) - Wilk, Barbara; Sahayaraj, Sylvester; Ziółek, Marcin; Babu, Vivek; Kudrawiec, Robert; Wojciechowski, Konrad
Abstract: Metal halide perovskites of reduced dimensionality constitute an interesting subcategory of the perovskite semiconductor family, which attract a lot of attention, primarily due to their excellent moisture resistance and peculiar optoelectronic properties. Specifically, quasi‐2D materials of the Ruddlesden–Popper (RP) type, are intensely investigated as photoactive layers in perovskite solar cells. Here, a scalable deposition of quasi‐2D perovskite thin films, with a nominal composition of 4F‐PEA2 MA4 Pb5 I16 (4‐FPEA + ‐4‐fluoro‐phenethylammonium, applied as a spacer cation), using an inkjet printing technique, is developed. An optimized precursor formulation, and appropriate post‐printing treatment, which enable good control over nucleation and crystal growth steps, result in highly crystalline and uniform perovskite layers. Particularly, vacuum with nitrogen flushing provides an optimal drying treatment, which produces a more uniform distribution of low dimensional phases, and a high level of vertical (out‐of‐plane) alignment, which is beneficial for charge carrier transport. Solar cells reaching 13% of power conversion efficiency for the rigid, and 10.6% for the flexible, large area (1 cm 2 ) devices are presented. Abstract : Scalable deposition of quasi‐2D perovskite thin films with an inkjet printing technique is developed. An optimized precursor formulation and appropriate post‐printing treatment enables good control over nucleation and crystal growth steps, resulting in uniformly distributed and vertically aligned perovskite grains. Solar cells reaching efficiency of 13% for the rigid, and 10.6% for the flexible, large area (1 cm 2 ) devices are presented.